Systematic Review on Adherence, Barriers to Treatment and Impact of Airway Clearance in Bronchiectasis - Low, Alyssa Yue Hui; Tan, Just Sen; Ganesan, Rethinam; Tan, Jaclyn; Lim, Albert Yick Hou (Archives of Clinical and Biomedical Research, 2020)
Background and objective: Chest physiotherapy (CPT) is an integral standard of treatment for patients with bronchiectasis. This study aims to analyse patients’ adherence to CPT, barriers to adherence and the impact on respiratory outcomes. Methods: A systematic literature review was conducted through electronic searches of Pubmed, Embase and Cochrane databases from 1st January 2010 to 20th March 2020 for adherence and or non-adherence rates to CPT of patients with cystic fibrosis (CF) and non-CF bronchiectasis (NCFB). Results: A total of thirteen publications with a study duration ranging from 1 to 16 months were qualified for inclusion. The paediatric population had a higher mean adherence rate than the adult population (range: 51% to 61% vs. 41% to 51%). The commonest CPT modalities were positive expiratory pressure (PEP) and flutter devices. Patients with high adherence of CPT had a significantly lower rate of hospitalisation than patients with low adherence rate (0.5 episodes/year vs. 1.4 episodes/year). A low adherence to CPT was associated with more pulmonary exacerbations. Patients with higher burden of treatment, perceived necessity of CPT and higher socio-economic status were more adherent to CPT. However, the effect of adherence to CPT on lung function and the quality of life (QoL) was inconclusive. Conclusions: The current literature suggests that adherence rate to CPT is poor amongst patients with NCFB and CF. There is a greater need for better understanding of the clinical consequences and economic impact of CPT on patients with NCFB.